2016
DOI: 10.3390/photonics3020020
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Crystal Quality of AlxIn1-xAsySb1-y for Terahertz Quantum Cascade Lasers

Abstract: Abstract:This work provides a detailed study on the growth of Al x In 1-x As y Sb 1-y lattice-matched to InAs by Molecular Beam Epitaxy. In order to find the conditions which lead to high crystal quality deep within the miscibility gap, Al x In 1-x As y Sb 1-y with x = 0.462 was grown at different growth temperatures as well as As 2 and Sb 2 beam equivalent pressures. The crystal quality of the grown layers was examined by high-resolution X-ray diffraction and atomic force microscopy. It was found that the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…4−7 However, some recent work has demonstrated methods for achieving high quality AlInAsSb films. Zederbauer et al have improved AlInAsSb random alloy growth on InAs, 8 which exhibits similar challenges to growth on GaSb. Most pertinent to the work described here, though, Vaughn et al have recently shown that stable AlInAsSb can be grown well within the miscibility gap by molecular beam epitaxy (MBE) as a digital alloy of the component binaries, AlAs, AlSb, InAs, and InSb.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4−7 However, some recent work has demonstrated methods for achieving high quality AlInAsSb films. Zederbauer et al have improved AlInAsSb random alloy growth on InAs, 8 which exhibits similar challenges to growth on GaSb. Most pertinent to the work described here, though, Vaughn et al have recently shown that stable AlInAsSb can be grown well within the miscibility gap by molecular beam epitaxy (MBE) as a digital alloy of the component binaries, AlAs, AlSb, InAs, and InSb.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite the many possible applications for Al x In 1– x As y Sb 1– y alloys lattice-matched to GaSb (henceforth referred to as AlInAsSb) in mid-infrared (IR) and near-IR optoelectronic devices, the growth and optoelectronic properties of this alloy have remained largely unexplored, due mostly to the presence of a wide miscibility gap. Mostly, InAs/AlSb superlattices have been utilized in place of AlInAsSb, such as in interband cascade lasers. However, some recent work has demonstrated methods for achieving high quality AlInAsSb films. Zederbauer et al have improved AlInAsSb random alloy growth on InAs, which exhibits similar challenges to growth on GaSb. Most pertinent to the work described here, though, Vaughn et al have recently shown that stable AlInAsSb can be grown well within the miscibility gap by molecular beam epitaxy (MBE) as a digital alloy of the component binaries, AlAs, AlSb, InAs, and InSb. Using this approach, mid-IR InAsSb/AlInAsSb type-I diode lasers have previously been demonstrated. , However, these previous studies were limited to Al fractions ranging from 0% to 40%, and photoluminescence (PL) was only observed up to Al fractions of 30%.…”
Section: Introductionmentioning
confidence: 99%
“…These reactions at the growth surface can be suppressed by lowering the substrate temperature below 430 °C . For the growth of GaAs 1‐x Sb x , the crystal quality can furthermore be improved by using higher Ga fluxes, but at the cost of accuracy regarding the layer thicknesses, as discussed in section 4.…”
Section: Growth Optimizationmentioning
confidence: 99%
“…However, these photodetectors not only necessitate complex material growth but also need a complicated procedure for fabrication of the device, which exhibits high cost and toxicity. [3,4] In contrast, photodetectors based on the Al x In 1−x AsSb (henceforth referred to as AlInAsSb) quaternary compound are promising candidates for both optoelectronic and electronic devices due to their flexibility to tune the bandgap and band offsets of heterostructures lattice matched to InP, [5] InAs [6,7] or GaSb [8,9] substrates. Varying the aluminum content tuned the bandgap from 0.25 eV (0% aluminum) to 1.18 eV (72% aluminum), corresponding to photon wavelengths from 5 µm to 1.05 µm.…”
Section: Introductionmentioning
confidence: 99%